Impact of obesity on atherogenic index in young adult females in Gadag, Karnataka - M., Margaret Mary; M. K., Jayalakshmi (International Journal of Research in Medical Sciences, 2024)
Background: Obesity is one of the most blatantly apparent, yet most disregarded, public health challenges in the present times. The prevalence of abdominal obesity in India was resolved to be 40% in females in India in the NFHS 5 survey. The gynaecological and reproductive fitness of women living with obesity is significant with changes demanded for precautionary health screenings. Obesity is a significant hazard factor for and contributor to accelerated morbidity and mortality, originally from cardiovascular complications and metabolic disorders. The rise in cardiovascular events has demanded the identification of practicable predictors that can assist in foretelling atherogenicity. Methods: This cross-sectional study was done between May 2022 to April 2024, in Gadag Institute of Medical Sciences, Gadag which comprised 240 female participants between the age of 18-40 years who were overweight/obese. Anthropometric parameters were measured and serum levels of lipid profile parameters were analysed Atherogenic Index was calculated. Results: Fat mass showed the strongest correlation with atherogenic index (r = 0.261), followed by fat mass index (r = 0. 257), BMI (r = 0.167) and body fat index (0.141). Free fat mass showed the least correlation (r = -0.074). Conclusions: Obesity and raised anthropometric parameters lead to an unfavourable lipid profile pattern and raises values of the atherogenic index.